The Mechanism of Detergent Solubilization of Lipid Bilayers - Lichtenberg, Dov (The Biophysical Society, 2013)
Multiple data are available on the self-assembly of mixtures of bilayer-forming amphiphiles, particularly phospholipids and micelle-forming amphiphiles, commonly denoted detergents. The structure of such mixed assemblies has been thoroughly investigated, described in phase diagrams, and theoretically rationalized in terms of the balance between the large spontaneous curvature of the curvophilic detergent and the curvophobic phospholipids. In this critical review, we discuss the mechanism of this process and try to explain the actual mechanism involved in solubilization. Interestingly, membrane solubilization by some detergents is relatively slow and the common attribute of these detergents is that their trans-bilayer movement, commonly denoted flip-flop, is very slow. Only detergents that can flip into the inner monolayer cause relatively rapid solubilization of detergent-saturated bilayers. This occurs via the following sequence of events: 1), relatively rapid penetration of detergent monomers into the outer monolayer; 2), trans-membrane equilibration of detergent monomers between the two monolayers; 3), saturation of the bilayer by detergents and consequent permeabilization of the membrane; and 4), transition of the whole bilayer to thread-like mixed micelles. When the detergent cannot flip to the inner monolayer, the outer monolayer becomes unstable due to mass imbalance between the monolayers and inclusion of the curvophilic detergent molecules in a flat surface. Consequently, the outer monolayer forms mixed micellar structures within the outer monolayer. Shedding of these micelles into the aqueous solution results in partial solubilization. The consequent leakage of detergent into the liposome results in trans-membrane equilibration of detergent and subsequent micellization through the rapid bilayer-saturation mechanism.